2019
DOI: 10.1016/j.vaccine.2019.05.049
|View full text |Cite|
|
Sign up to set email alerts
|

Seroprevalence and durability of rubella virus antibodies in a highly immunized population

Abstract: Background: Although the administration of the measles-mumps-rubella (MMR) vaccine has been widespread in the United States for decades, gaps in vaccine coverage still persist for various reasons. The maintenance of herd immunity against rubella virus (RV) is important to controlling the spread and resurgence of rubella and congenital rubella syndrome. Methods: In this study, we sought to assess the seroprevalence of RV-specific antibodies in an adult population from a defined geographic area in Olmsted County… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…The methods described below are similar or identical to those published for our previous studies [13,15,16,18,19,[61][62][63][64].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods described below are similar or identical to those published for our previous studies [13,15,16,18,19,[61][62][63][64].…”
Section: Methodsmentioning
confidence: 99%
“…Although rubella vaccine is effective for the majority of the population, data from the literature reveal sub-optimal long-term immunity and antibody titers below the level of protection (antibody titer <10 IU/mL) in a number of vaccinated subjects (ranging from 2 to 17%) who have received one or more doses of rubella-containing vaccine [4][5][6][7][8][9][10][11][12][13][14][15][16]. These findings suggest antibody waning and may indicate an increased subsequent risk for rubella among adolescents and adults (including women of childbearing age) years after vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Waning immunity for measles has been well-established in HIV-infected children, in particular if antiretroviral therapy has been interrupted [88]. For rubella, previous studies have shown that following two doses of MMR vaccine during childhood, the seropositivity rates remained high in young adults but antibody concentrations declined below protective levels in some individuals, which could have implications for the prevention of rubella in pregnancy [157][158][159].…”
Section: Secondary Vaccination Failurementioning
confidence: 99%
“…Many countries of the world have introduced Rubella vaccine (which is a Live attenuated virus vaccine) into their routine immunization programs and some have made the measlesmumps -rubella (MMR) vaccines readily available to protect their population, especially females of childbearing age against this infection. This has led to Rubella been verified as eliminated in the whole region of the Americas in 2015 6,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of Rubella through vaccination is still largely unavailable in Africa. As at June 2017, only 18 countries in Africa have introduced Rubella containing vaccines (RCV) into their Routine immunization programs 10 as against only two in 2010 2 . However, Nigeria being the most populous country in Africa has not introduced Rubella vaccine into its immunization program but with the support of WHO, nationwide Rubella surveillance has been set up simultaneously with the elimination-standard surveillance for measles for more than a decade.…”
Section: Introductionmentioning
confidence: 99%